2009
DOI: 10.3390/ijerph6041298
|View full text |Cite
|
Sign up to set email alerts
|

A School-Based Environmental Intervention to Reduce Smoking among High School Students: The Acadiana Coalition of Teens against Tobacco (ACTT)

Abstract: A school-based environmental program to reduce adolescent smoking was conducted in 20 schools (10 intervention; 10 control) in south central Louisiana. The 9 th grade cohort (n = 4,763; mean age = 15.4 yrs; 51% female; 61% Caucasian; 30-day smoking prevalence at baseline = 25%) was followed over four years for 30-day smoking prevalence with the school as the unit of analysis. Although prevalence decreased in intervention schools and increased in control schools in Year 2 the significant difference between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…The randomized controlled trials (RCT) were critically appraised using “Critical Appraisal Skills Program guidelines.” 13 All the nonrandomized studies were critically appraised using guidelines from Evaluating Research Articles From Start to Finish . 14 Out of 37 articles, 30 were RCTs, 15-44 and the remaining were nonrandomized trials. 45-51 They were accordingly given a score ranging from 0 to 10.…”
Section: Methodsmentioning
confidence: 99%
“…The randomized controlled trials (RCT) were critically appraised using “Critical Appraisal Skills Program guidelines.” 13 All the nonrandomized studies were critically appraised using guidelines from Evaluating Research Articles From Start to Finish . 14 Out of 37 articles, 30 were RCTs, 15-44 and the remaining were nonrandomized trials. 45-51 They were accordingly given a score ranging from 0 to 10.…”
Section: Methodsmentioning
confidence: 99%
“…Also the existing studies about the effects of psychodrama are limited to the number of mental and or social health issues. Therefore, it is suggested that some studies be conducted on other topics, such as lack of coping mechanisms (Llorca, Malonda & Samper 2017), smoking control programs (Carolyn 2009), use of drug substances (Karatay and Gürarslan, 2017), and body dissatisfaction (Thompson et al 1999). The study of mental health including the feelings and emotions and also their influences in the people's behavior has gained popularity among researchers in the last decades (Llorca, Malonda & Samper 2017).…”
Section: Discussionmentioning
confidence: 99%
“…El presente trabajo informa de los resultados del cese del tabaquismo en puntos de seguimiento múltiples y, al igual que en otros estudios, se comprueba cómo el efecto disminuye progresivamente durante este período (Grimshaw y Stanton, 2007;Myers y Brown, 2005) de forma que la reincidencia temprana es un peligro obvio. De los tres controles realizados tras la intervención, la medición del consumo a los doce meses es el mejor indicador ya que evita los sesgos del consumo intermitente típico del tabaquismo adolescente (Burton et al, 2009;Grimshaw y Stanton, 2007;Hughes et al, 2003;Johnson et al, 2009). La respuesta verbal sobre la abstinencia que dan los participantes se ha controlado con la realización de cooximetrías en cada visita de control, con un buen resultado por parte de los no fumadores al obtener en todos los casos un resultado compatible con el cese del consumo.…”
Section: Discussionunclassified
“…Los programas escolares destinados a niños y jóvenes, muchos de ellos dirigidos a la prevención, son las intervenciones más ampliamente utilizadas y cuentan con una amplia experiencia; sin embargo, en los últimos años se ha cuestionado su eficacia (Barrueco et al, 2007). Por otro lado, las intervenciones individuales realizadas en adultos no tienen igual validez sobre los adolescentes fumadores dadas las diferencias en los patrones de consumo de tabaco, el estilo de vida y las actitudes hacia los servicios sanitario de este grupo etario (Grimshaw y Stanton, 2007;Johnson et al, 2009). Existe una gran variabilidad en la atención prestada a estos adolescentes fumadores así como una falta de información contrastada acerca de la efectividad de los protocolos de intervención para dejar de fumar (Barrueco et al, 2007;Grimshaw y Stanton, 2007).…”
unclassified